2020
DOI: 10.7554/elife.58910
|View full text |Cite
|
Sign up to set email alerts
|

S-phase-independent silencing establishment in Saccharomyces cerevisiae

Abstract: The establishment of silent chromatin, a heterochromatin-like structure at HML and HMR in Saccharomyces cerevisiae, depends on progression through S phase of the cell cycle, but the molecular nature of this requirement has remained elusive despite intensive study. Using high-resolution chromatin immunoprecipitation and single-molecule RNA analysis, we found that silencing establishment proceeded via gradual repression of transcription in individual cells over several cell cycles, and that the cell-cycle-regula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 84 publications
2
17
1
Order By: Relevance
“…In contrast to H2A-P, SIR recruitment and silencing establishment is a slow process, with Sir3 and Sir4 binding increasing significantly after 90 min and accumulating over several cell cycles, leading to gene silencing only after long-term induction (20 h). This slow establishment of silencing is in contrast with previous reports monitoring silencing establishment at HM loci [ 24 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 50 ]. This difference could be explained by several factors: (i) the chromosomal position of the reporter studied (euchromatic regions 339 kb away from Tel2R in our system versus subtelomeric HML loci); (ii) the strength of the gene promoter [ 30 ]; (iii) the method used to induce silencing establishment.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to H2A-P, SIR recruitment and silencing establishment is a slow process, with Sir3 and Sir4 binding increasing significantly after 90 min and accumulating over several cell cycles, leading to gene silencing only after long-term induction (20 h). This slow establishment of silencing is in contrast with previous reports monitoring silencing establishment at HM loci [ 24 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 50 ]. This difference could be explained by several factors: (i) the chromosomal position of the reporter studied (euchromatic regions 339 kb away from Tel2R in our system versus subtelomeric HML loci); (ii) the strength of the gene promoter [ 30 ]; (iii) the method used to induce silencing establishment.…”
Section: Discussioncontrasting
confidence: 99%
“…Binding and unbinding of the LacI protein could increase the turnover of nucleosomes independently of DNA replication, thus leading to the incorporation of unmodified histones that are more permissive to Sir3 binding. In particular, H3K79 tri-methylation, which is widespread in euchromatin, counteracts Sir3 spreading and prevents silencing establishment [ 5 , 32 , 52 ]. Given the lack of enzyme to erase this histone mark, its removal can be achieved only through turnover of the histones that bear it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study found that Sir-based silencing establishment at both HML and HMR occurs through an intermediate silenced state, rather than an abrupt switch from the fully expressed to fully silenced state (Goodnight and Rine 2020). Furthermore, this intermediate state could be generated and stably maintained when certain histone modifying enzymes were absent in G1-arrested cells.…”
Section: The Existence Of An Intermediate Silenced Statementioning
confidence: 99%